2020
DOI: 10.1007/s10096-020-03848-1
|View full text |Cite
|
Sign up to set email alerts
|

The increased recurrence rate of liver abscess caused by extended-spectrum β-lactamase-producing Klebsiella pneumoniae

Abstract: Background The pathogenic bacterium Klebsiella pneumoniae (KP) is the major causative agent of pyogenic liver abscess (PLA). But reports about the prognosis of KP-caused PLA (KPLA) are rare. This study aimed to ascertain the recurrence rate of KPLA after initial treatment, and its contributing factors. Methods The medical records data were retrospectively analyzed of KPLA patients who were admitted to Shengjing Hospital of China Medical University from January 2012 to January 2018. According to whether or not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…In the past two decades, Klebsiella pneumoniae has been identified as the predominant pathogen of PLA in Asia [ 3 ]. Klebsiella pneumoniae -caused liver abscess (KPLA) was first reported in the 1980s in Taiwan [ 4 ], and the incidence of Klebsiella pneumoniae causing PLA was from 30% in the 1980s to over 80% in the 1990s among all causal pathogens [ 5 ]. KPLA is associated with several risk factors, such as diabetes, biliary tract disease and history of malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…In the past two decades, Klebsiella pneumoniae has been identified as the predominant pathogen of PLA in Asia [ 3 ]. Klebsiella pneumoniae -caused liver abscess (KPLA) was first reported in the 1980s in Taiwan [ 4 ], and the incidence of Klebsiella pneumoniae causing PLA was from 30% in the 1980s to over 80% in the 1990s among all causal pathogens [ 5 ]. KPLA is associated with several risk factors, such as diabetes, biliary tract disease and history of malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…Septic pulmonary embolism caused by a K. pneumoniae liver abscess combined with the metastatic infection of other vital organs confers a poor prognosis [28]. It found that K. pneumoniae was the main pathogen that caused the bacterial liver abscess, compared with E. coli [29][30][31]. In a retrospective study, a total of 102 nonrepetitive strains of bacteria from 178 patients were isolated, including Klebsiella pneumoniae (82 strains, 80.3%), Escherichia coli (8 strains), Pseudomonas aeruginosa (2 strains), Acinetobacter baumannii (1 strain), and Gram-positive cocci (9 strains).…”
Section: Discussionmentioning
confidence: 99%
“…Of the iuc+ isolates, (42). These invasive infections are associated with significant mortality and morbidity; patients with PLA take longer to recover and 9-18% have recurrent PLA (43,44). In addition, one study showed that 10/14 patients with endogenous endophthalmitis progressed to blindness (45).…”
Section: Discussionmentioning
confidence: 99%
“…The invasive nature of hvKP strains allow them to cause unusual infections such as PLA, endogenous endophthalmitis, necrotizing fasciitis, and meningitis associated with clinical implications distinct from those of the more common cKP strains (33). For example, 9-18% of PLA patients have a recurrence of their infection (74,75), suggesting that prolonged treatment courses may be necessary. In one study, 10 of 14 patients with endogenous endophthalmitis progressed to blindness (76), underscoring that these infections are medical emergencies.…”
Section: Discussionmentioning
confidence: 99%